An initial psychometric evaluation of the German PROMIS v1.2 Physical Function item bank in patients with a wide range of health conditions. (January 2018) - Liegl, Gregor; Rose, Matthias; Correia, Helena; Fischer, H Felix; Kanlidere, Sibel; Mierke, Annett; Obbarius, Alexander; Nolte, Sandra
Objectives: To translate the PROMIS Physical Function (PF) item bank version 1.2 into German and to investigate psychometric properties of resulting full bank and seven derived short forms. Design: Cross-sectional psychometric study. Setting: Inpatient and outpatient clinics of the Department of Psychosomatic Medicine at Charité–Universitätsmedizin Berlin, Germany. Subjects: A total of 10 adult patients with various chronic diseases participated in cognitive debriefing interviews. The final item bank was administered to n = 266 adult patients with a broad range of medical conditions. Interventions: Patient-reported outcome assessment as part of routine care. Main measures: PROMIS v1.2 PF bank; MOS SF-36 PF scale (PF-10). Results: Cross-cultural adaptation of the item bank followed established guidelines. For the final German translation, the corrected item-total correlations ranged from 0.44 to 0.84. Cronbach's alpha was high for each PROMIS PF short form ( α = 0.88–0.96). The full PROMIS PF bank and most short forms correlated highly with the SF-36 PF-10 ( r = 0.85–0.90), with the exception of PROMIS Upper Extremity ( r = 0.64). PROMIS Upper Extremity showed ceiling effects and lower agreement with the full bank than other short forms. Unidimensionality was supported for all PROMIS PF measures using traditional factor analysis and nonparametric item response theory. Conclusion: The German PROMIS PF bank was found to be conceptually equivalent to the English version and fulfilled the psychometric requirements for use of short forms in clinical practice. Future studies should pay particular attention to samples with upper extremity functional limitations to further investigate the dimensional structure of PF as conceptualized according to PROMIS.